The Expression of Chicken Anemia Virus Vp3 Gene and Induction of Apoptosis In Transformed and Tumor Cells - Ghrici, Mohamed (2001)
The pathogenicity of chicken anemia virus (CAV), as shown in previous studies, is the function of apoptotic mechanism as observed in chicken thymocytes and transformed chicken-lymphoblastoid T cells. Thus the present study aimed to investigate the gene and its gene product responsible for apoptosis in as such that leads to the destruction of affected cells. It is known that apoptosis process is an important natural physiological mechanism that induces killing of cancer cells. Therefore, in theory, the gene or its gene product that is responsible for the apoptotic mechanism could be exploited especially in cancer therapy. In this study, a complete open reading frame (ORF) encoding VP3 protein was obtained from the DNA extracted from archival paraffin-embedded tissues and cloned into a plasmid vector. The sequencing of the full length of the ORF encoding VP3 protein showed that it was 363 base pairs long, which is similar in size to that of the reference CA V Cux-l strain. Comparison of the nucleotide sequences of this VP3 gene with that of the CAV Cux-l strain exhibited 98% sequence homology indicating that these two viruses are closely related. The functional characteristics of VP3 gene were further investigated by using an eukaryotic expression system, plasmid pcDNA 3.1/Zeo+. The purified recombinant pcDNA-VP3 plasmid was used to transfect mammalian cells and cancer cells via electroporation. The induction of apoptosis, upon expression of VP3 gene, was studied by identifying and detecting morphological and biochemical changes due to apoptosis. Upon electron microscopic examination, typical apoptotic features were observed, which includes nuclear margination and formation of apoptotic bodies, as early as two days after transfection. Morphological changes developed due to apoptosis were obvious which were later confirmed by means of the apoptotic biochemical staining and DNA fragmentation assay. The differential activities of VP3 were further investigated by the use of the immunofluorescence technique. The VP3 protein was expressed and detected only in the cytoplasm of normal cells. In contrast, the expression of VP3 protein was localized particularly in the nucleus of the transformed cell lines (Vero and rat embryo fibroblast cells) and human derived breast cancer cells (MCF-7 and MDAMB 231). This differential cellular localization of VP3 protein in normal versus tumorigenic and transformed cells was the reason of VP3 specifically inducing apoptosis in transformed and cancerous cells but not in normal cells. The effects of VP3 protein expression in these three types of cells were also confirmed upon examination by confocal microscopy analysis with cells stained in propidium iodide and acridine orange stains. In conclusion, VP3 protein expression alone was able to induce apoptosis in transformed cells and in human derived cancer cells but had no effect on normal cells. The substantial evidences indicated that the DNA construct containing the VP3 gene under the control of human cytomegalovirus (hCMV) promoter, alias in the form of a DNA vaccine is the new potential candidate for anticancer therapy.